Levels of Pathogenic Th17 and Th22 Cells in Patients with Rheumatoid Arthritis - Marlen Vitales-Noyola; Berenice Hernández-Castro; Diana Alvarado-Hernández; Lourdes Baranda; Sofía Bernal-Silva; Carlos Abud-Mendoza; Perla Niño-Moreno; Roberto González-Amaro (Journal of Immunology Research)
Rheumatoid arthritis (RA) is a chronic autoimmune condition characterized, among others, by tissue damage and activation/differentiation of proinflammatory lymphocytes. Accordingly, several studies have concluded that type 17 T helper (Th17) cells seem to have an important role in the pathogenesis of this condition. However, the strategy for the identification and analysis of proinflammatory Th17 cells in those studies has not been consistent and has usually been different from what was originally described. Therefore, we decided to evaluate the levels of Th17 cells in patients with RA employing an extended immune phenotype by using an eight-color multiparametric flow cytometry analysis. For this purpose, blood samples were obtained from 30 patients with RA and 16 healthy subjects, and the levels of Th17 and type 22 helper (Th22) lymphocytes were analyzed as well as the in vitro differentiation of peripheral blood mononuclear cells into Th17 lymphocytes induced by interleukin-23 (IL-23) and IL-1β. We found significant enhanced levels of total Th17 lymphocytes (defined as CD4+IL-17+) as well as enhanced numbers of their pathogenic (defined as CD4+CXCR3+IL-17+IL-22+CD243+CD161+IFN-γ+IL-10-) and nonpathogenic (CD4+CXCR3+IL-17+IL-22-CD243-CD161-IFN-γ-IL-10+) cell subsets in patients with RA. Likewise, the number of Th22 (CD4+CXCR3+/-IL-17-IL-22+) was also increased in these patients compared to healthy controls. However, the in vitro induction/differentiation of pathogenic Th17 cells showed similar results in controls and patients with RA. Likewise, no significant associations were detected in patients with RA between the levels of Th17 or Th22 cells and clinical or laboratory parameters. Our data indicate that patients with RA show enhanced blood levels of the different subsets of Th17 cells and Th22 lymphocytes tested in this study and suggest that these levels are not apparently associated with clinical or laboratory parameters.